REKONSTRUKSI KONSEP JUSTICIABILITY: KAJIAN NORMATIF ATAS HUKUM KEPAILITAN DI INDONESIA - Anggie Danielle Rumondang Bulan Purba; Muhammad Fauzi; Grizelda Grizelda (Universitas Labuhanbatu, 2026)
Indonesia’s bankruptcy regulation under the Bankruptcy and Suspension of Debt Payment Obligations Law (UUK-PKPU) still contains fundamental problems due to overly simple formal requirements and the absence of an insolvency test mechanism. This condition causes bankruptcy proceedings to be frequently used as an instrument of pressure against debtors, giving rise to “pseudo-bankruptcy” practices, obstructing business continuity, and reducing bankruptcy’s function as an ultimum remedium. Moreover, bankruptcy decisions often reflect administrative-formalistic considerations rather than substantive justice. This study aims to analyze the urgency of reconstructing the concept of justiciability within Indonesian bankruptcy law and to formulate an ideal concept of justiciability as the foundation of a fair bankruptcy system. This research employs a normative (doctrinal) legal method using statutory, conceptual, and comparative law approaches. The findings demonstrate that reconstructing the concept of justiciability is necessary to establish an objective, transparent, and equitable mechanism for selecting bankruptcy cases that protects both creditors and debtors. The ideal concept of justiciability in Indonesian bankruptcy law requires the implementation of solvency tests, substantive and procedural justice, clear hierarchy of claims, and more selective insolvency instruments. A comparison with bankruptcy systems in the United States, Thailand, and the Netherlands indicates that the application of insolvency tests can prevent abuse of bankruptcy mechanisms and enhance legal certainty. This study emphasizes that reconstructing the concept of justiciability is an essential step toward developing a more just, proportional, and non-formalistic bankruptcy system in Indonesia.Keywords: Reconstruction of Bankruptcy Law; Justiciability; Bankruptcy; Insolvency